Diagnostic significance of biomarkers content changes in the case of atherosclerotic involvement of branchiocephalic arteries among the patients with chronic cerebral ischemia - Демченко, Аліна Вікторівна (ScienceRise: Medical Science, 2016)
Aim of the work – to establish the diagnostic value of biomarkers content at atherosclerotic involvement of brachiocephalic vessels for optimization of diagnostic arrangements in patients with chronic cerebral ischemia (CCI). Material and methods of research. 355 patients with CCI (among them 230 women and 125 men, mean age - 55,30±7,91years) were examined using clinical-neuropsychological, biochemical, immune-enzyme and ultrasound methods of examination. Atherosclerotic plaques (AP) of brachiocephalic vessels are visualized in 155 (43,7 %) patients. Results. According to the results of research, the reliably lower concentrations of cholesterol of lipoproteins of the high density, stable metabolites NO, catalases and increased contents of fibrinogen, homocysteine and ketodin nitrofenol hydrazones were established in the blood serum of patients with CCI at AP and also the essential changes in concentration of renewed glutathione in both plasma and hemolysate of erythrocytes and increase of activity of glutathione reductase in hemolysate of erythrocytes and glutathione peroxidase in the blood plasma were registered. The decrease of concentration of stable metabolites of nitrogen oxide at increase of AP number was established. Conclusions. The correlations were revealed between AP and the content of spontaneous ketodin nitrofenol hydrazones, homocysteine, cholesterol of lipoproteins of the high density, triglycerides, stable metabolites NO, and also activity of glutathione peroxidase in the blood plasma that testifies to the joint participation of studied biomarkers in atherosclerotic involvement of brachiocephalic vessels